(untitled) (Globalization and Business, 2023)
The aim of the present study is to consider a range of problems that are to be solved during the implementation of the projects aimed at increasing the access to healthcare and based on the achievements of the new technological order on the example of Latvia, primarily the e-health project. Since January1, 2018, the use of the e-health system in Latvia is mandatory, but so far only the “Digital Prescription (e-prescription)” project has been functioning at full capacity. The experience with the introduction and the use of digital medicine in Latvia indicates a large range of problems faced by state institutions and local self-government institutions, medical establishments, medical personnel and patients. A systematic vision of the problems of implementing digital medicine requires a necessity, at least, of taking into account and solving seven relatively independent tasks: technical and technological, economic, legal, organizational, managerial, social, psychological, and cultural ones. In terms of systemic vision, the assessment of these aspects of the e-health programme implementation is presented by means of an extensive use of data retrieved from international organizations, Latvian state statistics, scientific research studies, including the ones carried out by the authors. The main conclusion of the study is the need for the theory and the practice of the increasing access to healthcare based on digital medicine, taking into account a more complete variety of factors that stimulate and constrain this process, and involving specialists from the sphere of social sciences. The importance of the problem has significantly increased amid COVID-19 crisis. So far, there are no relevant statistics on the availability of medical services during the pandemic, but individual assessments and recommendations of specialists indicate the need for a speedy and coordinated global promotion of e-health. The example of Latvia demonstrates that there are significant barriers to e-health. An accelerated decision process regarding the given issue is not always related to the economic resources of the country. Our studies show the importance of solving institutional problems, ensuring the better mainstreaming of psychological, sociocultural and social factors. In our opinion, the upcoming project by the Latvian researchers “Latvia. Human Development Report” should be devoted to the most topical issue of e-health. While working on this project, it would be crucial to use the experience of specialists from other countries where similar studies have been conducted (Georgia, Ukraine, Poland, etc.) and experience of international cooperation in the framework of other social projects has already been accumulated.